2015
DOI: 10.1128/aac.03719-14
|View full text |Cite
|
Sign up to set email alerts
|

Metallo-β-Lactamase-Producing Bacteroides Species Can Shield Other Members of the Gut Microbiota from Antibiotics

Abstract: Antibiotics disrupt the intestinal microbiota, rendering patients vulnerable to colonization by exogenous pathogens. Intermicrobial interactions may attenuate this effect. Incubation with ceftriaxone-resistant, ccrA-positive, ␤-lactamase-producing Bacteroides strains raised the minimum bactericidal concentration of ceftriaxone required to kill a susceptible Escherichia coli strain (mean change, <0.25 to 29 mg/liter; P ‫؍‬ 0.009); incubation with ceftriaxone-resistant but non-␤-lactamase-producing Bacteroides s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 17 publications
0
20
0
Order By: Relevance
“…A recent study found that β-lactamase-producing Bacteroides spp. were able to shield a β-lactamase-negative E. coli isolate from the activity of ceftriaxone [29]. Likewise, we have shown that a β-lactamase-positive Prevotella isolate protected a susceptible P. aeruginosa isolate from the action of ceftazidime.…”
Section: Discussionmentioning
confidence: 82%
“…A recent study found that β-lactamase-producing Bacteroides spp. were able to shield a β-lactamase-negative E. coli isolate from the activity of ceftriaxone [29]. Likewise, we have shown that a β-lactamase-positive Prevotella isolate protected a susceptible P. aeruginosa isolate from the action of ceftazidime.…”
Section: Discussionmentioning
confidence: 82%
“…First, Acidaminococcus and other Negativicutes have been found in clinical samples and may be involved in polymicrobial infections like abscesses (Jumas-Bilak et al, 2007;Tito et al, 2017), dysbiotic conditions like vaginosis (Zozaya-Hinchliffe et al, 2008), or complex disorders (Gough et al, 2015;Nam et al, 2018). Second, the secretion of betalactamases into the gut by commensal bacteria in response to beta-lactam antibiotics prescribed against bacterial pathogens could provide resistance for nearby bacteria, including pathogens, by collective resistance, sometimes termed indirect or passive resistance (Stiefel et al, 2015;Sorg et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Bacteroides or Prevotella species producing beta-lactamases that protected the microbiota when a beta-lactam was given 20,21,35,36 . Our results call for further experiments to identify protective species with ARDs of low human risk concern 27 that could potentially be included in synthetic microbiota as "bodyguards" for the bacteria of interest.…”
Section: Discussionmentioning
confidence: 99%